Efficiency in the Public Sector 2002
DOI: 10.1007/978-1-4757-3592-5_11
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency in the Provision of Municipal Nursing- and Home-Care Services: The Norwegian Experience

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…The algorithms described in this paper have been tested with the use of real-life data sets from different areas: Russian banks, Norwegian municipal nursing-and home-care services and Swedish electricity utilities. Original data sets are described in papers [5,6,8]. Computational results are illustrated in this paper on the data from Swedish electricity utilities.…”
Section: Computational Experimentsmentioning
confidence: 99%
“…The algorithms described in this paper have been tested with the use of real-life data sets from different areas: Russian banks, Norwegian municipal nursing-and home-care services and Swedish electricity utilities. Original data sets are described in papers [5,6,8]. Computational results are illustrated in this paper on the data from Swedish electricity utilities.…”
Section: Computational Experimentsmentioning
confidence: 99%
“…Despite these problems, there are several applications of DEA to the nursing home industry, including Fizel and Nunnikhoven (1992), Dully et al (1994), Erlandsen and Forsund (1999), Kooreman (1994), Nyman andBricker (1989) andSOA Associates (2003). In particular, Nyman and Bricker (1989) use DEA to calculate efficiency scores for184 nursing facilities in Wisconsin in 1979.…”
Section: Modeling Technical Efficiencymentioning
confidence: 99%
“…Although many studies have investigated efficiency in long-term care provision, there are relatively few studies on a regional long-term care system managed by a local public entity, which is the focus of this study. The latter include literature on municipalities (e.g., Erlandsen & Førsund, 2002 ; Hougaard et al, 2004 ; Laine et al, 2005 ; Borge et al, 2009 ). To elucidate the structure of cost inefficiency, we apply the formula used by Thanassoulis et al (2012) , which is a modification of the method suggested by Tone (2002) and Tone and Tsutsui (2007) , and we deconstruct cost efficiency into technical, allocative, and price efficiencies.…”
Section: Introductionmentioning
confidence: 99%